Effect of low-temperature annealing on light-emitting properties of na-Si/SiOx porous nanocomposite films - Lisovskyy, I.P.; Litovchenko, V.G.; Zlobin, S.O.; Voitovych, M.V.; Khatsevich, I.M.; Indutnyy, I.Z.; Shepeliavyi, P.E.; Kolomys, O.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The effect of low-temperature annealing on light emitting properties of naSi/SiOx porous column-like nanocomposite films has been studied. Influence of type of chemically active gas or inert ambient on PL characteristics is shown. Existence of metastable defects in such structures is shown. A temperature interval for healing the metastable defects is defined. Mechanisms to reduce a non-radiative recombination channel depending on the gas ambient are proposed.